Maternal adverse childhood experiences, current cumulative risk, and behavioral dysregulation among child welfare involved children. (December 2019) - Greenfield, Brett; Williams-Butler, Abigail; Fay, Kathleen Pirozzolo; Duron, Jacquelynn F.; Bosk, Emily Adlin; Stepleton, Kate; Mackenzie, Michael J.
The intergenerational influence of adverse childhood experiences on individual outcomes demonstrates a need for research that considers both personal and environmental contributors to risk. As such, the current study explored how maternal cumulative risks influence the relationship between maternal Adverse Childhood Experiences (ACEs) and their children's behavioral dysregulation among families involved with the child welfare system ( N = 314). The importance of child age is also considered. The sample was stratified by age groups of children (1.5–5 years and 6–18 years), and the relationship between maternal ACEs, cumulative risk, and child behavior was assessed using OLS regressions. For younger children, maternal ACEs were only associated with externalizing behaviors when not controlling for cumulative risk, but cumulative risks were independently and significantly associated with both internalizing and externalizing behaviors. For older children, ACEs were independently associated with both types of behavior, but controlling for cumulative risk attenuated the strength of this relationship. Cumulative risks were also independently associated with older children's internalizing and externalizing behaviors. Findings suggest the need to consider both individual and environmental risks for parents and children involved in the child welfare system, and the developmental timing and stability of that risk, in order to adequately support parent-child relationships as well as caregiving environments.